A socio-economic study for the manufacture of medicinal and aromatic plants in Lattakia Governorate - العلوني, إيمان; محسن جحجاح , (Latakia University Journal -Biological Sciences Series, 2023)
Therefore, the importance of the research is to focus on encouraging and developing the manufacture of medicinal and aromatic plants A study of the social characteristics of medicinal and aromatic plant growers in Lattakia Governorate. Studying the economic and marketing efficiency of medicinal and aromatic plants manufacturing facilities in Lattakia Governorate, "Bloran Manufacturing Unit" as a model. It was found that the percentage of illiterates in all the studied villages was non-existent, while it was found that the highest percentage of holders of a primary certificate was in the villages of Qardaha, which amounted to 14.03%, and the percentage of those who obtained a secondary certificate was the highest, reaching 68.57% in the villages of Lattakia, while the percentage of those who obtained a certificate varied. University, as it reached 20.91% in the studied villages of Jableh, and despite the varying educational status of individuals in the villages of the study, this did not affect their knowledge of the importance of medicinal and aromatic plants, and their benefits, as everyone has sufficient knowledge and awareness of the need to preserve wild species, and increase the area planted from it. It was noted that the average yield of male and female medicinal and aromatic plants are not equal, and therefore there is an effect of the gender of the respondents on the yield of cultivation.The total annual costs of the facility amounted to about 46084500 SP/year. The total net profit amounted to about 17542725 SP.